A Rational Deconstruction of Landin's J Operator - Danvy, Olivier; Millikin, Kevin (BRICS Report Series, 2006)
Landin's J operator was the first control operator for functional languages, and was specified with an extension of the SECD machine. Through a series of meaning-preserving transformations (transformation into continuation-passing style (CPS) and defunctionalization) and their left inverses (transformation into direct style and refunctionalization), we present a compositional evaluation function corresponding to this extension of the SECD machine. We then characterize the J operator in terms of CPS and in terms of delimited-control operators in the CPS hierarchy. Finally, we present a motivated wish to see Landin's name added to the list of co-discoverers of continuations.